Detection and Analysis of Active Compounds in Ni gella sativa and Senna alata through Biological Methods (The Peerian Journal, 2024)
The study is centered on compounds derived from Nigella sativa and Senna alata; extraction, identification and quantification methods of which are the focus of this study together with a focus on newer analytical techniques. These plants are known for their healing properties, namely, bactericidal, anti-inflammatory and anti-oxidative activity. The study seeks to observe these compounds with a view of determining their capacity in the creation of therapies